Community-Based Solar Panel Installation and Maintenance Training for Energy Independence in the Riau Islands - Sophie Vermeer; Sulaiman Sulaiman; Anna Bakker (Yayasan Adra Karima Hubbi, 2025)
The Riau Islands, like many regions in Indonesia, faces challenges related to energy access and sustainability. Despite efforts to improve energy infrastructure, remote communities continue to struggle with reliable power supply, especially in rural and isolated areas. In response to these challenges, the research explores the potential of community-based solar panel installation and maintenance training as a solution to promote energy independence and sustainability. The study aims to assess the effectiveness of training programs in empowering local communities to independently manage and maintain solar energy systems. Using a mixed-methods approach, the research employed both qualitative and quantitative methods to evaluate the impact of the training. Surveys and interviews were conducted with participants from selected communities in the Riau Islands to measure knowledge acquisition, skill development, and the sustainability of the solar panels installed. The results indicate significant improvements in local capacity to install and maintain solar energy systems, leading to enhanced energy independence and reduced reliance on external sources. The study concludes that community-based solar panel training programs can significantly contribute to energy sustainability in remote regions, empowering local populations to take control of their energy needs. The research underscores the importance of investing in renewable energy education as part of broader efforts to achieve energy independence in Indonesia.